2020
DOI: 10.3390/app10113728
|View full text |Cite
|
Sign up to set email alerts
|

The Cytotoxic Effect of Newly Synthesized Ferrocenes against Cervical Carcinoma Cells Alone and in Combination with Radiotherapy

Abstract: Cervical cancer is one of the most common types of cancer in women, with approximately 500,000 new cases and 250,000 deaths every year. Radiotherapy combined with chemotherapy represents the treatment of choice for advanced cervical carcinomas. The role of the chemotherapy is to increase the sensitivity of the cancer cells to irradiation. Cisplatin, the most commonly used drug for this purpose, has its limitations. Thus, we used a family of ferrocene derivatives (in addition, one new species was prepared using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…In this context, two research studies and one review paper published in this Special Issue are representative of this idea. The first, by Skoupilova et al [15] reported a series of ferrocene derivatives from the general formula [Fe(η 5 -C 5 H 4 CH 2 (p-C 6 H 4 )CH 2 (N-het)) 2 ], which bear either substituted or unsubstituted saturated five-and six-membered nitrogencontaining heterocycles that are able to inhibit the cervical cancer cell growth, with or without the contemporaneous exposure to ionizing radiation. The authors demonstrated that these complexes possessed higher anticancer activity than Cisplatin, which was used as reference, and that the exposure to an ionizing radiation increased the anticancer properties, probably because of a radiosensitizing phenomenon that should be further investigated.…”
Section: Contributionsmentioning
confidence: 99%
“…In this context, two research studies and one review paper published in this Special Issue are representative of this idea. The first, by Skoupilova et al [15] reported a series of ferrocene derivatives from the general formula [Fe(η 5 -C 5 H 4 CH 2 (p-C 6 H 4 )CH 2 (N-het)) 2 ], which bear either substituted or unsubstituted saturated five-and six-membered nitrogencontaining heterocycles that are able to inhibit the cervical cancer cell growth, with or without the contemporaneous exposure to ionizing radiation. The authors demonstrated that these complexes possessed higher anticancer activity than Cisplatin, which was used as reference, and that the exposure to an ionizing radiation increased the anticancer properties, probably because of a radiosensitizing phenomenon that should be further investigated.…”
Section: Contributionsmentioning
confidence: 99%
“…The mechanism of their action relies either on the interaction with genomic DNA or the modulation of DNA metabolism. An alternative approach is based on the IR potentiation by drugs increasing intracellular levels of reactive oxygen species (ROS), e.g., sorafenib [ 9 ], l -S-buthionine (BSO) [ 10 ], As 2 O 3 [ 11 ], diisopropylamine dichloroacetate (DADA) [ 12 ] and ferrocene derivatives [ 13 , 14 ]. However, despite their high antitumor efficacy, these drugs also affect healthy tissues and cells, which so far precludes potential clinical applications of RT approaches based on ROS-regulation.…”
Section: Introductionmentioning
confidence: 99%